Photo-driven growth of a monolayer of platinum spherical-nanocrowns uniformly coated on a membrane toward fuel cell applications. Issue 44 (22nd October 2020) - Liu, Huiyuan; Qin, Jiaqi; Rockward, Tommy; Wu, Jingtian; Li, Jia; Li, Guangwei; Mao, Qing; Lv, Yang; Wang, Xiao; Zhang, Shuomeng; Shi, Weiyu; Chen, Gang; et al.
Abstract : Membrane electrode assemblies with ordered electrocatalyst layers are fabricated by regio-selective growth of a monolayer of platinum spherical nanocrowns on a photocatalyst-decorated membrane under irradiation. Abstract : Membrane electrode assemblies (MEAs) serve as the core units of polymer electrolyte membrane fuel cells (PEMFCs) and are regularly fabricated by painting a slurry of commercial Pt/C onto a membrane, leading to thick and disordered electrocatalyst layers (CLs). Herein, we report a photo-driven fabrication of MEAs with ultra-thin and ordered CLs by growing a monolayer of dendritic platinum spherical nanocrowns onto each side of a photocatalyst-modified membrane. This approach allows us to control the thickness and platinum loading of ordered CLs by simply varying the concentration of the platinum precursor under tungsten light irradiation. The resultant MEAs exhibit an excellent fuel cell power density of 1.01 ± 0.05 W cm −2 at a platinum loading of 53 ± 1.5 μg cmcathode −2 . This exceptional activity likely arises from the nanostructured platinum crowns, efficient mass transport, and uniform reaction rate in the ultrathin (59 ± 12 nm thick) and ordered CLs according to electrochemical and theoretical investigations.